Investigating Patient Satisfaction in Wound Care at NCI Clinic Samarinda - Edwin, Edward; Tan, Jacob Donald (Jurnal Locus Penelitian dan Pengabdian, 2026)
Wound care is a critical aspect of healthcare, particularly in communities facing an increasing prevalence of chronic and post-surgical wounds. In Samarinda, East Kalimantan, the growing demand for specialized wound care services highlights the need to understand patient satisfaction as a vital indicator of healthcare quality. This study aimed to investigate the factors influencing patient satisfaction at NCI Wound Care Clinic, which provides both in-clinic and home-care wound management. A qualitative case study approach was employed, involving eight informants: four who received treatment at the clinic and four who received home-care services. Data were collected through semi-structured in-depth interviews, direct observations, and field notes, and were analyzed thematically. The findings identified seven latent variables that influenced satisfaction: engaging interpersonal communication, accessibility from home, perceived clinical competence of nurses, detailed pricing, accommodation of personal needs, and two negative factors—ineffective registration and scheduling processes. The results indicate that empathy, professionalism, transparency, and flexibility contribute significantly to patient satisfaction. Conversely, administrative inefficiencies negatively affect satisfaction and perceptions of service quality. The study concludes that improving interpersonal communication, cost transparency, and digitalized administrative systems can enhance both patient satisfaction and the overall quality of wound care services.